Introduction of a care bundle effectively and sustainably reduces patient-reported surgical site infection in patients undergoing colorectal surgery. Issue 2 (June 2020) - Dean, H.F.; King, E.; Gane, D.; Hocking, D.; Rogers, J.; Pullyblank, A.
Summary: Background: Surgical site infection (SSI) is one of the most common healthcare-associated infections and is particularly prevalent following colorectal surgery. It is associated with an increase in patient morbidity and healthcare costs. SSI is difficult to monitor as it frequently presents after discharge from hospital, especially if enhanced recovery programmes are in place. Aim: To develop an effective method for measuring patient-reported 30-day SSI in patients undergoing colorectal resection. To implement a new care bundle capable of delivering a sustainable reduction in SSI. Methods: The Public Health England SSI surveillance questionnaire was used. Several data collection methods were tested including postal and telephone-based systems. A new SSI bundle was introduced in our centre incorporating four evidence-based interventions: 2% chlorhexidine skin preparation; repeat-dose antibiotics after 4 h; dual-ring wound protectors; and triclosan-coated sutures for wound closure. System changes were introduced to ensure that the change was sustainable. Findings: The most reliable method of measuring patient-reported SSI was found to be postal questionnaire with telephone calls made to non-responders. Response rates to the SSI surveillance questionnaire were consistently >75%. Introduction of the new care bundle produced a significant reduction in SSI from 20% to 10% ( P ≤ 0.0001) which has been sustained for six years. Conclusion: This is a reliable method for measuring 30-day patient-reported SSI rates. The introduction of this new care bundle has halved the rate of SSI from 20% to 10%.